Is My House My Home? An Analysis of "Nowhereness" Among "Noknowers" in Transitional Settings. Issue 4 (November 2019) - Subasinghe, Chamila
This study investigates the concept of home versus house among people who have been forcibly evicted from their long-term homes and are living in transitional settings due to the conflict in northeastern Sri Lanka. The discourse is built on two common notions related to liminalities of internally displaced people's (IDP's) transitional setting: "nowhereness" and "noknowers." The study examines the causes and consequences of IDP's perceived "nowhereness" in an unfamiliar physical setting, which in turn makes them "noknowers" in an unsupportive social setting. Transcripts from in-depth, open-ended interviews with IDPs are interpolated and categorized to distil themes among core meanings attached to the home. Though these IDPs were originally interviewed to ascertain their sense of home in the transitional shelter, many interviewees ended up focusing on nostalgic memories of their lost homes. The transitional shelter is not a home, but rather an indefinite process of making a home from sociocultural residues.